Komunikasi Non Verbal Anak Autis pada Masa Adaptasi Pra Sekolah : Komunikasi Non Verbal Anak Autis pada Masa Adaptasi Pra Sekolah - Mutia Rahmi Pratiwi; Lisa Mardiana; Amida Yusriana (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Every children has distinguished life, likewise the life of the children with autism. Children with autism frequently considered as odd because they seems like having trouble in paying attention and are uninterested to social life. Indonesia does not have the precise number of the children with autism and it has been increased every year. Education is one of the medium for children with autism to learn the standard way of behaviour that socially acceptable. The kindergarten is the first non formal school for children with autism. However, the autism’s disability often fails the communication process at school. The rejection will be unavoidable for the first initial meetings. This phenomenon becomes the main attraction for the researcher to analyze the behaviour of children with autism in the kindergarten. This is a qualitative research and using the phenomenology method. The objects of the research is M, W and D. They are the children with autism at the informal school of Widya Bhakti Semarang. The aim of this research is to describe the non verbal communication of children with autism as the efforts of adaptation in the kindergarten.